PENGARUH RELOKASI TERHADAP PENDAPATAN BULANAN PEDAGANG KAKI LIMA PAKAIAN DI PASAR RAYA FASE VII KOTA PADANG - Enjel Tia Falma; Bigharta Bekti Susetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to analyze the effect of relocation on the monthly income of clothing street vendors in Pasar Raya Phase VII, Padang City. The background of this study is based on the phenomenon of relocation of street vendors from the main road area to the basement of the Phase VII building carried out by the Padang City government to organize the market area to be more orderly and comfortable. This study uses a descriptive quantitative approach with a sample of 96 respondents selected using simple random sampling techniques. Research data were collected through observation, questionnaires with a Likert scale and documentation. The results showed that relocation had a negative and significant effect on the monthly income of clothing street vendors. The regression coefficient value of -0.437 and the coefficient of determination (R2) of 0.334 indicated that 33.4% of the decrease in monthly income was influenced by the relocation factor. Based on the individual sample t-test, it is known that the significance value (Sig.) of 0.000 is smaller than 0.05, so H0 is rejected and Ha is accepted and it can be concluded that relocation has a significant effect on the decrease in income of clothing street vendors in Pasar Raya Phase VII, Padang City. These findings recommend the need for policies and support for post-relocation vendor adaptation.